1160 Which parameters do correlate better with functional exercise capacity in children with repaired Tetralogy of Fallot? An echo and CMR study. (17th January 2020) - Avesani, M; Borrelli, N; Filippini, E; Delle Donne, G; Krupickova, S; Josen, M; Iliceto, S; Di Salvo, G
Abstract: Background: Severe pulmonary regurgitation (PR) and progressive right ventricular (RV) disfunction are common in patients with repaired Tetralogy of Fallot (r-TOF), and CMR has become the gold standard for PR and RV volumes assessment. However, in paediatric patients CMR use can be limited by the need for general anaesthesia. Purpose: The aim of our study was to analyse a paediatric population (<18 years) of r-TOF with at least moderate PR (regurgitant fraction (RF) >20%), assessed by CMR and to assess which Echo or CMR parameter is associated with functional capacity evaluated by cardiopulmonary exercise test (CPET). Methods: Consecutive r-TOF patients regularly followed at our Institution, with at least moderate PR (RF >20% by CMR), were included in the study. Echocardiographic and CMR studies were performed within six months. Echo study: PR was assessed by Color Doppler, continuous-wave (CW) Doppler and derived parameters such as pressure half time (PHT), PR index, ratio of diastolic and systolic time-velocity integrals (DSTVI) of the main pulmonary artery. RV end-diastolic area (RVEDA), end-systolic area (RVESA), right ventricle outflow tract (RVOT) end-diastolic area, fractional area change (FAC) and TAPSE were calculated. By speckle tracking analysis we measured also RV global longitudinal strain (RVGLS) and right atrial strain (RAS). CMR study: we evaluated PR as RF, end-diastolic and systolic volumes (RVEDV, RVESV) and right ventricle ejection fraction (RVEF). In addition, patients underwent CPET within one month from CMR and peak oxygen consumption (Vo2) values were measured. Results: We studied 53 r-TOF patients (aged 13.8 ± 2.5 years, ranged between 7.1 and 17.6 years, male 57%, surgical repair at a mean age of 1.1 ± 0.75 years). Based on CMR data, 38 out of 53 had free PR (RF >35%) and nobody had > mild tricuspid regurgitation. We found a good correlation between RVEDA and CMR RVEDV (p <0.0001, r =0.73), which slightly improved adding RVOT area (p < 0.0001, r =0.75). RVEDA indexed (RVEDAi) > 21.3 cm2/mq was found to have a good sensitivity (83.3%, specificity 64.9%, AUC0.74) for RVEDV indexed (RVEDVi) >150 ml/mq. No correlation was found between TAPSE, FAC, RVGLS measured by echo and RVEF calculated by CMR. No correlation was found between echo Doppler parameters used to assess PR severity and PR RF measured by CMR. None of the CMR studied parameters (RV volumes, RVEF, RF) correlated with peak Vo2. Among the Echo parameters only RAS demonstrated a good correlation (p <0.0001, r =0.70) with peak Vo2. At the multivariate analysis including RAS, TAPSE, FAC, RVGLS, RVEF and RVEDV, RAS was the best independent predictor of peak Vo2 (p <0.0001). Conclusion: Echo parameters studied to assess PR are unsatisfactory and showed no correlation with PR RF by CMR. RVEDAi is well correlated with CMR volumes. Right atrial strain is the best predictor of peak Vo2 in young patients with r-TOF and should be included in their follow up.